Ethical and social implications of the introduction of the vaccine against the human papilloma virus in Mexico: reflections on a proposed intervention - Prieto de la Rosa, Alejandra; Gutiérrez Delgado, Cristina; Feinholz Klip, Dafna; Morales González, Gisela; Witlen, Renee (Acta Bioethica, 2008)
The objective of this work is to identify ethical and social aspects related to the introduction of the vaccine against the human papillomavirus (HPV) in Mexico for an informed and just decision that considers not only financial aspects. According to information about the efficiency and cost of the vaccine, its introduction to the public health system of Mexico can lead to unforeseen consequences for the participants and for society as a whole. The introduction of the vaccine should examine the Mexican context, recognizing its risks without overestimating potential or proven results derived from diverse vaccine policies. Exposing scientific evidence and the motives for decision making is essential. Also, it is essential to take a responsible stand toward political decisions on the implementation of vaccine programs, screening and treatment for cervical cancer based on the potential for new technologies to save lives, always with respect for the rights, opinions and preoccupations of women, the recipients of the HPV vaccine, and that represent an added value for Mexican society as a whole.